ANALISIS PENERAPAN PSAK NO.30 (REVISI 2011) ATAS AKUNTANSI LEASING PADA PT. FEDERAL INTERNATIONAL FINANCE (FIF) CABANG MANADO - Husain, Yusni; Wokas, Heince (ACCOUNTABILITY, 2016)
PT. Federal International Finance (FIF) is a credit financing institution engaged in the business of credit financing. PT. FIF provides credit services to customers with expected profits derived from loan interest, so PT. FIF has a good amount of lease receivables. Therefore, any application of lease accounting in accordance with SFAS 30 (Revised 2011) on lease accounting. This study aims to determine the application of lease accounting PT. FIF. The research method used comparative descriptive method. The results showed the application of PT. FIF has been in accordance with the applicable standards. In recognition of finance lease PT. FIF has been in accordance with the applicable accounting standards for finance leases are recognized at fair value, net of transaction costs that occur. PT. FIF use leasing capital lease accounting model, can be seen from the provisions of the lease on the company's letter, stating their option rights for the lease upon expiration of the lease, where the provisions of this falls in the existing criteria on capital lease. In the final days of capital lease rental payments, the option to lease the vehicle ownership. PT. FIF use leasing capital lease accounting model by the method of direct financing leases or direct financing method.